Turbinaria conoides Extract Increases the Storability of Red Nile Fillet at Cold Temperatures - Amir Husni; Latif Sahubawa; Imam Arda Perdana (Jurnal Perikanan Universitas Gadjah Mada, 2019)
The aim of the research was to assess the effect of Turbinaria conoides extract as a natural antibacterial agents on shelf life of red tilapia fillet at low temperature. The fresh red tilapia fillet soaked with a Turbinaria conoides extract solution for 30 minutes at various concentration of 0.0%; 0.5%: 1.0%; 1.5% and 2.0%, than stored at low temperature (4°C) for 12 days with four days interval observation, repeteadly. The parameter observed wereTotal Plate Count (TPC), Total Volatile Base (TVB), pH and scoring. The result showed that Turbinaria conoides extract able to maintain shelf life of red tilapia fillet at low temperature up to 12 days based on the content of TPC and TVB. Turbinaria conoides extract can maintain the score of appearance and texture of red tilapia up to 8 days. The treatment 1.5% of Turbinaria conoides extract was the best treatment in maintaining shelf life of red tilapia fillet at low temperature based on the parameters of TPC, TVB, appearance and texture.